2022
DOI: 10.1177/01430343221144407
|View full text |Cite
|
Sign up to set email alerts
|

Risks and opportunities for children's well-being in resource-constrained multigenerational households during COVID-19: Implications for school psychology interventions

Abstract: The coronavirus disease (COVID-19) pandemic had a global impact on family social and economic well-being. Individuals and families sought alternative living arrangements as a result of the financial crisis, health implications, and housing insecurity, with many joining multigenerational households. However, it is unknown how multigenerational family life affects children's well-being. Therefore, this qualitative study explored risks and resilience-building opportunities for children's psychological and social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…While the papers in this special issue showed that parents, other caregivers (e.g., grandparents-see Mohangi, 2022), and teachers are important co-champions of student resilience, they also flagged the importance of SPs nurturing the resilience of these co-champions. Luthar et al (2020) 2022) paper showed that purposeful capacitation of teachers and school staff yields dividends for student wellbeing.…”
Section: Schools As Caring Communities With a Commitment To Student R...mentioning
confidence: 99%
See 4 more Smart Citations
“…While the papers in this special issue showed that parents, other caregivers (e.g., grandparents-see Mohangi, 2022), and teachers are important co-champions of student resilience, they also flagged the importance of SPs nurturing the resilience of these co-champions. Luthar et al (2020) 2022) paper showed that purposeful capacitation of teachers and school staff yields dividends for student wellbeing.…”
Section: Schools As Caring Communities With a Commitment To Student R...mentioning
confidence: 99%
“…For instance, Mohangi's (2022) study, which included five African family units, underscored the importance of extended family members (like grandparents) to how students' households coped with family violence and acute financial stress. In addition, some participants in Mohangi's (2022) study referred to their grandparents teaching them to pray. Participants in Pillay's (2022) study also reported that spiritual resources were important resilience enablers.…”
Section: Schools As Caring Communities With a Commitment To Student R...mentioning
confidence: 99%
See 3 more Smart Citations